Épocas de consórcio de alho com cenoura em três sistemas de manejo de plantas daninhas em Jaboticabal-SP - Mueller, S.; Durigan, J.c. [UNESP]; Kreuz, C.l.; Banzatto, D.a. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2001)
This work was carried out using intercropped cultivation of garlic (Allium sativum) and carrot (Daucus carota) in Jaboticabal, SP - Brazil. Four seeding timings for carrot (0, 15, 30 and 45 days after garlic planting) and three weed management systems (herbicide, frequent manual weed control and no weed control) were tested. The effects of this intercropped system on weed control, efficient land use and productivity were determined. The experimental design was a completely randomized block with split-plots and four replications, with carrot seeding timings being the plots and the weed management systems, the sub-plots. The herbicide oxadiazon at 750 g ha-1 did not cause toxicity in the garlic, nor in the carrot plants. Regandress of the timing for the intercropping establishment the Land Equivalent Ratio (LER) values were greater than one. Garlic-carrot intercropping profitability was greater than that of monocultures of garlic crop, mainly under weed management systems, using the herbicide oxadiazon and frequent manual weeding.

Com o objetivo de estudar o sistema de cultivo consorciado das culturas de alho (Allium sativum) e cenoura (Daucus carota) no município de Jaboticabal-SP, testaram-se quatro épocas de semeadura da cenoura (0, 15, 30 e 45 dias após o plantio do alho) combinadas com três manejos de plantas daninhas (herbicida, capinas freqüentes e sem controle). Determinaram-se os efeitos deste consórcio no controle de plantas daninhas, no uso eficiente da terra (UET) e na rentabilidade agrícola. Utilizou-se o delineamento experimental de blocos casualizados, dispostos em parcelas subdivididas, com quatro repetições. As épocas foram as parcelas e os manejos as subparcelas. O herbicida oxadiazon a 750 g ha-1 não causou sintomas de intoxicação às plantas de alho e cenoura. Todos os tratamentos de épocas de início de consórcio, dentro dos três manejos de plantas daninhas, apresentaram valores de UET maiores que 1. A rentabilidade do consórcio de alho e cenoura foi maior que a do monocultivo de alho, em qualquer época e principalmente dentro do manejo com oxadiazon.
Garlic-carrot intercropping timing under three weed management systems in Jaboticabal-SP
Keywords: Allium sativum; Daucus carota; manejo de plantas daninhas; uso eficiente da terra; Allium sativum; Daucus carota; weed management; land equivalent ratio